(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The basal hadrosauroid Tethyshadros insularis from the uppermost Cretaceous of NE Italy lived on an island of the European archipelago in the Tethys Ocean. The tail of this dinosaur presents several apomorphic traits respect to the tails of other coeval hadrosauroids of the archipelago and of hadrosauroids in general. The estimated total length of the tail of the holotypic specimen shows that the tail was long, accounting for at least 56% of the total body length, relatively stiff and deep proximally, whereas it was whip-like distally. The reconstruction of the tail musculature by comparison with that of living archosaurs and other dinosaurs suggests that the posterior shift of the first haemapophysis affected the size and shape of the M.m. caudofemorales with important consequences on the locomotion of T. insularis. Somewhat peculiar stance and gait for this dinosaur are suggested also by limb features. The posterior shift of the vent and consequent longer distal tract of the intestine or a longer cloaca could increase the space for urine storage and urinary water reabsorption. The posterior shift of the vent could imply also longer oviducts and plausibly an increased number of eggs per clutch. Tail apomorphies of T. insularis may be related to the rugged and water-depleted karst landscape where the Italian dinosaur lived. The two main specimens of T. insularis differ in robustness possibly because of sexual dimorphism, ontogeny or high intraspecific variability.